Using the gRPC protocol in the context of crisis management - Lozić, Davor; Bralić, Vladimir; Filipović, Antun Matija (Crisis Management Days, 2025)
Speed, stability, and efficiency are key parameters in inter-service communication during crisis management. Traditionally, REST, an architectural style based on HTTP protocol principles was used in microservice architecture due to its simplicity and broad support. However, with the increasing number of requests to and between microservices, the gRPC protocol is becoming an increasingly attractive alternative. This paper presents the technical advantages of the gRPC protocol over traditional REST in the context of inter-service communication in crisis conditions, focusing on several key parameters: low latency, efficiency, data streaming capability, and support for distributed transactions. This paper demonstrates the gRPC protocol through the Go programming language, which is also recognized as a very efficient, reliable, and scalable, making it acceptable for microservices development.